1999
DOI: 10.1073/pnas.96.14.7791
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of cyclin T1/P-TEFb to an HIV type 1 long terminal repeat promoter proximal RNA target is both necessary and sufficient for full activation of transcription

Abstract: Transcriptional activation of the HIV type 1 (HIV-1) long terminal repeat (LTR) promoter element by the viral Tat protein is an essential step in the HIV-1 life cycle. Tat function is mediated by the TAR RNA target element encoded within the LTR and is known to require the recruitment of a complex consisting of Tat and the cyclin T1 (CycT1) component of positive transcription elongation factor b (P-TEFb) to TAR. Here, we demonstrate that both TAR and Tat become entirely dispensable for activation of the HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 49 publications
4
146
1
Order By: Relevance
“…Maximal activities obtained with the Hex⅐Tat48 or LaRP7⅐Tat48 chimeras were somewhat lower (5-to 8-fold) than those obtained with other systems, such as Rev and SLIIB (20-to 30-fold) (34,35,37,44). This difference could reflect the ability of Rev to form higher-order oligomers that recruit more activators to the elongation complex.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Maximal activities obtained with the Hex⅐Tat48 or LaRP7⅐Tat48 chimeras were somewhat lower (5-to 8-fold) than those obtained with other systems, such as Rev and SLIIB (20-to 30-fold) (34,35,37,44). This difference could reflect the ability of Rev to form higher-order oligomers that recruit more activators to the elongation complex.…”
Section: Discussionmentioning
confidence: 53%
“…In these systems, the TAR in the HIV LTR is replaced by an RNA sequence of interest (34), and RNA-binding proteins that interact with it are used as fusion partners of specific effectors. One well studied plasmid target contains the stem-loop IIB (SLIIB) from the HIV Rev response element and Rev proteins fused to activators of transcription elongation (35,37,44). In particular, CycT1 from P-TEFb is a strong activator when fused to Rev, as are the transcriptional activation domain of Tat (residues 1-48, TAD48) and RelA, a subunit of nuclear factor B (44, 45).…”
Section: Hexim1 and Larp7mentioning
confidence: 99%
“…Under similar conditions, CycT1-Tat bound all three s U TAR RNA sequences with varying efficiencies of RNA-protein complex formation: 75% with s U31 TAR, 60% with s U33 TAR, and 30% with A30-s U34 TAR. We used CycT1(1-303) in these RNA gel-shift assays instead of P-TEFb for three reasons: (i) this region of CycT1 is sufficient to form stable complexes with Tat-TAR and CDK9 (8,(10)(11)(12)(13)(14)(19)(20)(21), (ii) the kinase subunit CDK9 does not interfere with CycT1 specificity for Tat-TAR binding (8,(10)(11)(12)(13)(14)(19)(20)(21), and (iii) detection of the CycT1(1-303)-Tat-TAR complex by native gel electrophoresis methods is more straightforward and reliable compared with P-TEFb-Tat-TAR or CycT1(1-726)-Tat-TAR complexes. These results indicate that all 4-thiouridine-containing RNA sequences can form complexes with CycT1-Tat.…”
Section: Cyct1mentioning
confidence: 99%
“…Recruitment of P-TEFb to TAR has been proposed to be both necessary and sufficient for activating transcription elongation from the HIV-1 long terminal repeat promoter (10). Neither CycT1 nor the P-TEFb complex bind TAR RNA in the absence of Tat; thus TAR binding is highly cooperative for both Tat and P-TEFb (7,9).…”
mentioning
confidence: 99%
“…Tat interacts with the cyclin T1 (CycT1) subunit of P-TEFb and recruits the kinase complex to TAR RNA. Recruitment of P-TEFb to TAR has been proposed to be both necessary and sufficient to activate transcription elongation from the HIV-1 long terminal repeat promoter (13). Recent fluorescence resonance energy transfer studies, using fluorescein-labeled TAR RNA and a rhodamine-labeled Tat protein, showed that CycT1 remodels the structure of Tat to enhance its affinity for TAR RNA, and that TAR RNA further enhances interaction between Tat and CycT1 (14).…”
mentioning
confidence: 99%